2009
DOI: 10.1179/030192309x12492910938131
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion characterisation – tool for measurement of steel cleanliness and process control: Part 1

Abstract: Owing to increasing demand for high surface and internal quality finished steel products, it is imperative to study the factors that limit the production of such steels. In particular, non-metallic inclusions affect steel cleanliness and cause defects leading to worsening of desired mechanical properties and service life of steel products. Other detrimental effects of inclusions are poor steel castability often resulting in slab downgrades and rejections, increased costs associated with recycling of liquid ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…This is well established in steelmaking practices, where the cast steel samples can be directly used, given the abundant numbers of small inclusions typically present. For instance, Kaushik, Pielet and Yin [5], recently reported on the use of an Automated SEM system. These are now in common use within the steel in dustry for assessing steel cleanliness.…”
Section: Optical Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is well established in steelmaking practices, where the cast steel samples can be directly used, given the abundant numbers of small inclusions typically present. For instance, Kaushik, Pielet and Yin [5], recently reported on the use of an Automated SEM system. These are now in common use within the steel in dustry for assessing steel cleanliness.…”
Section: Optical Methodsmentioning
confidence: 98%
“…This equation states that the mass of an inclusion, multiplied by its ac celeration, is equal to the sum of: 1) the standard drag force exerted on the particle owing to relative motion between the local liquid velocity within the ESZ and the particle, together with 2) the "added mass" force which must be included if a particle is accelerating, or decelerat ing, relative to the fluid, 3) the fluid acceleration term, a history term (4), a buoyancy term (5), and an electromag netic force term (6). The dominant force terms applying to particles travelling through the ESZ's are the standard drag force, the added mass force, and the electromagnetic force.…”
Section: Theory Of Inclusion Motion Through Eszmentioning
confidence: 99%
“…The background information on formation of alumina inclusion morphologies is reported elsewhere 2–12; the work of Wasai 3, Pielet 7 and Tiekink 8–10 motivated this study. Recently, Tiekink et.al 10 concluded that morphologies of alumina inclusions from either deoxidation or reoxidation are similar – the clustering effect is likely an effect of agglomeration or growth of smaller particles.…”
Section: Introductionmentioning
confidence: 96%
“…These steels are also known for their clogging tendency 1 due to the presence of both endogenous and exogenous inclusions. Sometimes the steel cleanliness, defined by either total oxygen content or inclusion density in tundish samples 2, is also compromised due to minor variations in the secondary refining practices leading to downgrading and rejection of entire or significant tonnage from the heat. One indicator which was used to determine the relative steel cleanliness at an ArcelorMittal steel‐producing plant was the oxygen activity before steel deoxidation at the Rurhsthal Heraeus (RH) degasser.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, complete removal of harmful inclusions from molten steel during the refining process is difficult. An alternative approach is to minimise the harmful effects of residual inclusions or to beneficially utilise these inclusions through proper control and modification.…”
Section: Introductionmentioning
confidence: 99%